2017
DOI: 10.1016/j.ydbio.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 defect in escort cells triggers germline tumor in Drosophila ovary

Abstract: Drosophila ovary is recognized as one of the best model systems to study stem cell biology in vivo. We had previously identified an autonomous role of the histone H1 in germline stem cell (GSC) maintenance. Here, we found that histone H1 depletion in escort cells (ECs) resulted in an increase of spectrosome-containing cells (SCCs), an ovary tumor-like phenotype. Further analysis showed that the Dpp pathway is excessively activated in these SCC cells, while the expression of bam is attenuated. In the H1-deplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Previous studies have also shown that UGC accumulation caused by extrinsic EC defects is always coupled with severe loss of ECs 10,2426,28,46 , indicating that a certain number of EC is required for non-cell autonomous control of germline differentiation. To determine whether Tj controls EC number, the enhancer trap line PZ1444 52,53 , which labels both CpCs and ECs, was used to directly quantify the EC number in germaria.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies have also shown that UGC accumulation caused by extrinsic EC defects is always coupled with severe loss of ECs 10,2426,28,46 , indicating that a certain number of EC is required for non-cell autonomous control of germline differentiation. To determine whether Tj controls EC number, the enhancer trap line PZ1444 52,53 , which labels both CpCs and ECs, was used to directly quantify the EC number in germaria.…”
Section: Resultsmentioning
confidence: 93%
“…What motivates the ectopic BMP activity outside the GSC niche? Several correlative studies suggest complex mechanisms, in which a population of ECs is capable of expressing Dpp as well as other niche cell markers under certain conditions 20,21,25,26,28 . Together, they reveal that tightly regulated dpp transcription is required to maintain homeostasis of adult ovaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis is needed to investigate whether these proteins actually bind to endogenous TSC22D1 family proteins under intracellular physiological conditions and to examine functional interactions, but it was clear that histone H1 binds to TSC-22 (TSC22D1-2) or TSC22(86) (TSC22D1-3) in cells. Histone H1 is a linker histone and its overexpression induces an abnormal nuclear morphology and chromatin structure, which positively and negatively regulates transcription in vitro (Figure 8A) [20,[40][41][42][43]. We propose the possible mechanisms between the TSC22D1 family and histone H1 (Figure 8A).…”
Section: Discussionmentioning
confidence: 86%
“…The cystoblast continues to divide, with the end result being the production of 16-cell cysts in region 2b of the germarium (Spradling, 1993). Somatic ECs are typically quiescent and support the developing germline, with tight association of ECs with the germline being necessary for germline development (Banisch, Maimon, Dadosh, & Gilboa, 2017; Kirilly, Wang, & Xie, 2011; Maimon, Popliker, & Gilboa, 2014; Yang et al, 2017). ECs are highly dynamic in nature and protrude within the packed germarium to invade and engulf the germline (Banisch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%